Edukasi Hipertensi Pada Lansia Di Gereja Paroki Sant Antonius Purbayan, Surakarta - Aji, Sulistyani Prabu; Putri, Noviyati Rahardjo; Syarifah, Syarifah (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Hypertension is a degenerative disease known as a "silent killer" because it can appear without any signs and symptoms or warnings, so many people are not aware of it. Prevention and control of hypertension is important, and considering the increasing incidence and impact of hypertension, awareness and prevention efforts are needed so that elderly people without hypertension can avoid hypertension. This activity aims to provide health education about hypertension in the elderly group. The method of implementing elderly health service and elderly examination at the Sant Antonius Purbayan Surakarta Parish Church is in the form of education, discussion, questions and answers related to the definition, causative factors, signs and symptoms, and prevention and control of hypertension complications. This activity involved 101 elderly participants at the Purbayan Church. Based on the results of the interview, there was a significant difference in the level of knowledge of the elderly about hypertension before and after the activity. This change has a positive impact on increasing the knowledge of the elderly, which means that this community service activity is beneficial for the elderly group at the Purbayan Church, Surakarta.